The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/aogs.12287
|View full text |Cite
|
Sign up to set email alerts
|

Reduced quality of life when experiencing menstrual pain in women with primary dysmenorrhea

Abstract: Primary dysmenorrhea is the most common gynecological condition among women of reproductive age. Although dysmenorrhea has been reported to affect the ability of women to carry out daily activities, the impact of primary dysmenorrheic pain specifically on quality of life (QoL), has yet to be elucidated. We investigated whether QoL varies between women with and without severe primary dysmenorrhea, and whether QoL is impaired only during menstruation or also during pain‐free phases of the menstrual cycle. Twelve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
75
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 18 publications
5
75
1
9
Order By: Relevance
“…Collectively, these are common gynecological complications in women. Regardless of the cause, dysmenorrhea can have a substantial impact on patient quality of life,7,8 yet many patients do not seek treatment 9. In a patient survey, some untreated women have expressed feelings of resistance or aversion toward seeking therapy, and many suggested that gynecologist consultations were unnecessary for their disorder 1.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these are common gynecological complications in women. Regardless of the cause, dysmenorrhea can have a substantial impact on patient quality of life,7,8 yet many patients do not seek treatment 9. In a patient survey, some untreated women have expressed feelings of resistance or aversion toward seeking therapy, and many suggested that gynecologist consultations were unnecessary for their disorder 1.…”
Section: Introductionmentioning
confidence: 99%
“…This also applies to Japanese women [1416]. In addition to physiological characteristics, menstrual cycle-related symptoms affect health-related quality of life [17]. According to an epidemiological study, average scores of students with premenstrual syndrome were significantly lower in all domains of quality of life [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of dysmenorrhea varies greatly across different countries (16-91% [5][6][7]; of which, 2-40% report as being moderate to severe [4,8]. Dysmenorrhea is one of the most common menstrual disorders, and if accompanied by symptoms such as headache, fatigue, nausea, vomiting, diarrhea, impatience, chills, and muscle cramps can disrupt the quality of life and social activities of young women [9,10]. Primary dysmenorrhea is more common and has good prognosis.…”
Section: Introductionmentioning
confidence: 99%